'Isn't that too much data?!' Incorporating surveys into heritage tourism research design. (2015) - Reed, Ann
Survey research is an underutilised methodology in anthropology that could be quite useful in understanding how people find meaning in travel and tourism. This article foregrounds the use of surveys in conjunction with more established ethnographic techniques of participant-observation and interviewing. The author argues that using only ethnographic approaches runs the risk of reinforcing the dominant discourses found in public events and in interviews with key informants, whereas surveys can give voice to the voiceless and bring to light important details that would otherwise remain obscured from view. Significant features of two surveys used for research on Ghana's slavery heritage tourism are discussed in order to demonstrate exactly how surveys can be beneficial in tracking how widespread particular beliefs are, and in identifying how survey data can help to correct the taken-for-granted assumptions of ethnographers.